Acute stress responses of autonomous nervous system, HPA axis, and inflammatory system in posttraumatic stress disorder - von Majewski, Kristin; Kraus, Olga; Rhein, Cosima; Lieb, Marietta; Erim, Yesim; Rohleder, Nicolas (Translational Psychiatry, 2023)
Posttraumatic stress disorder (PTSD) does not only have direct consequences for well-being, but it also comes with a significant risk for severe somatic health consequences. A number of previous studies have pointed to alterations in stress systems in traumatized persons, as well as the inflammatory system, which might be important links in the pathway between trauma, PTSD, and health consequences. The aim of this study was to investigate acute stress responses in PTSD patients compared with healthy controls. Twenty-seven PTSD patients and 15 controls were exposed to the Trier Social Stress Test (TSST), and we measured salivary cortisol, salivary alpha-amylase (sAA), plasma interleukin-6 (IL-6), as well as heart rate and heart rate variability (HRV) at different time points before, during and after the stress test. Results revealed similar stress responses between patients and controls, but lower baseline cortisol levels and higher IL-6 baseline levels in PTSD patients. Increases in sAA stress responses were significantly lower in patients, while sAA concentrations were higher in the PTSD group during intervention. HRV was markedly decreased in patients and showed a significantly blunted acute stress response with a slower recovery after TSST. These results confirm previous findings of marked stress system dysregulations in PTSD and add to the literature on acute stress reactivity in PTSD which appears to show stress system-specific changes. Overall, these results have implications for our understanding of potential risk and resilience factors in the response to trauma.
CRIS-Team Scopus Importer:2023-02-10

Interleukin-6 secretion upon acute psychosocial stress as a potential predictor of psychotherapy outcome in posttraumatic stress disorder - Rhein, Cosima; Hepp, Tobias; Kraus, Olga; von Majewski, Kristin; Lieb, Marietta; Rohleder, Nicolas; Erim, Yesim (Journal of Neural Transmission, 2021)
Posttraumatic stress disorder (PTSD) is a severe mental disorder that can develop after a traumatic event. PTSD has been reported to be associated with activation of the innate immune system, as measured by increased levels of pro-inflammatory cytokines. While it is well known that PTSD patients display increased levels of interleukin 6 (IL-6) when compared with healthy controls, the relationship between cytokine secretion and treatment outcome has been hardly investigated yet. The aim of this study was to assess the potential association of inflammatory activation and therapy outcome in PTSD. Before therapeutic intervention, we applied the Trier Social Stress Test (TSST) as a method to elicit psychosocial stress and an acute inflammatory response. IL-6 levels were measured in blood plasma of PTSD patients at different time points before and after the TSST. Severity of depressive, trauma-related, and somatic symptoms was assessed before and 8 weeks after trauma-focused treatment in a multimodal day clinic setting. We showed that high reactivity of IL-6 to psychosocial stress at the beginning of the therapy was associated with a negative therapy outcome in PTSD, especially regarding depressive symptoms. This study suggests plasma IL-6 reactivity as a potential molecular marker to predict treatment outcome in PTSD.
CRIS-Team Scopus Importer:2021-05-28
Keywords: BDI-II; Interleukin 6; Posttraumatic stress disorder; Psychotherapy; Therapy outcome; Trier Social Stress Test

Peripheral inflammation over the course of a cognitive behavioral intervention in PTSD - von Majewski, Kristin; Rohleder, Nicolas; Ehring, Thomas (Brain, Behavior, & Immunity-Health, 2023)
Inflammation has an important predictive role for long-term health. This is also true when looking at the specific population of trauma survivors with PTSD. There are emerging findings showing that PTSD is related to reduced somatic health as well as evidence linking inflammation with disease outcomes in this group, such as heart diseases and early mortality, regardless of age, gender or conventional risk factors. The effectiveness of cognitive behavioral therapy for PTSD symptom severity has been demonstrated by several previous studies. In contrast, literature is scarce, yet, whether inflammation improves over the course of treatment for PTSD. Therefore, the aim of this study was to investigate whether not only PTSD symptoms, but also inflammation changes over the course of psychological treatment. Twenty-nine PTSD patients were followed while attending an outpatient clinic receiving cognitive behavioral therapy. Inflammation, determined by the C-reactive protein (CRP) assessed via the dried blood spot (DBS) technique, and symptom severity, surveyed by the PTSD Checklist for DSM-5 (PCL) were measured at 5 points before trauma-focused therapy, as well as after four, eight and twelve weeks of intervention; furthermore, a 10-month follow-up assessment was conducted. Results revealed significant improvements of PTSD symptom severity during investigation, but no significant changes in the inflammatory biomarker (CRP). Results in terms of improvement in PTSD symptom severity are in line with prior findings. The results obtained for inflammation may suggest that risk factors for somatic health consequences in PTSD patients remain despite successful psychological treatment. Further longitudinal studies are needed to fully understand the relationship between inflammation and therapeutic outcome and to develop interventions normalizing inflammation in PTSD patients.
CRIS-Team Scopus Importer:2023-04-28
Keywords: CBT; CRP; Inflammation; Inflammatory biomarker; Posttraumatic stress disorder; Psychological treatment; Trauma